A review and estimate of time spent in prison by offenders sentenced for murder - Nafekh, Mark; Flight, Jillian I. (Correctional Service Canada, Research Branch, 2002)
The purpose of the present study is to determine the average time offenders sentenced for murder spend in prison over three legislatively-relevant time periods : pre-1961 (pre-capital/non-capital murder sentences); 1961 to 1976 (capital/non-capital murder designation) and 1976 to 2002 (1st and 2nd degree murder designation)
OCLC: 1079860474